2009
DOI: 10.1002/ccd.22012
|View full text |Cite
|
Sign up to set email alerts
|

Leaking hepatic artery aneurysm successfully treated with covered stent

Abstract: Hepatic artery aneurysm (HAA) is rare with reported incidence of 0.02%. It accounts for approximately 12-20% of all visceral aneurysms. The reported risk of rupture ranges from 14% to 80% of all HAAs. Traditionally, HAA has been treated surgically or by transcatheter coil embolization. There are few published reports of percutaneous HAA stenting. We report a case of a 72-year-old female with leaking HAA who was successfully treated with endovascular stenting. The authors include a review of the relevant litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…1,5,8,9 Among the different forms of splanchnic vascular aneurysms, 1,2,4,8-10 only splenic artery aneurysms (60%-75%) are more frequent than HAA. Pseudoaneurysms of hepatic arteries in particular have been increasing in recent decades, and the rate of increase has paralleled the increase in interventional biliary procedures, such as biopsies, and nonoperative liver trauma (such as that caused by car accidents).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,5,8,9 Among the different forms of splanchnic vascular aneurysms, 1,2,4,8-10 only splenic artery aneurysms (60%-75%) are more frequent than HAA. Pseudoaneurysms of hepatic arteries in particular have been increasing in recent decades, and the rate of increase has paralleled the increase in interventional biliary procedures, such as biopsies, and nonoperative liver trauma (such as that caused by car accidents).…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5,9 It has been reported that extrahepatic aneurysms are located in the common hepatic artery in 63% of reported cases, in the right hepatic artery in 28% of cases, in the left hepatic artery in 5% of cases, and in both the right and left hepatic arteries in 4% of cases. [3][4][5]8,10 Furthermore, a general trend has been noted in which intrahepatic aneurysms tend to be located in the right hepatic artery. 4 The aneurysmal diameters reported have ranged between 1.5 and 14 cm, with the mean diameter being calculated at 3.6 cm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations